Effects of CO2 addition on deflagration characteristics of syngas-air premixed mixtures in T-pipeline. (29th October 2022) - Wei, Shengnan; Deng, Haoxin; Xu, Zhuangzhuang; Yan, Mengmeng; Wen, Xiaoping; Wang, Fahui; Chen, Guoyan
Abstract: With the industrial application of syngas, the explosion accident caused by it has gradually become a topic of concern for researchers. In this paper, the effects of CO2 addition on the deflagration characteristics of syngas-air premixed mixtures were investigated through experiments and numerical simulations. Experiments were carried out inside a T-pipeline, using a high-speed camera and a pressure sensor to simultaneously record the flame evolution and pressure dynamics during deflagration. Simulations were calculated using the GRI 3.0 mechanism by Chemkin Premix Code. The results show that the addition of CO2 has a certain inhibitory effect on the flame propagation, which can make the finger flame in the vertical pipe evolve into a "tulip" flame. And under the inhibition of CO2, the deflagration overpressure of the mixture is reduced, and the number of H, O, OH radicals is also greatly reduced, and the chemical reaction rate is correspondingly slowed down. Graphical abstract: Image 1 Highlights: The flame spreads symmetrically in the T-pipeline. The addition of CO2 can inhibit the flame propagation in the T-pipeline. The more CO2 added, the lower the T-pipeline explosion overpressure.